2019
DOI: 10.1002/elan.201900328
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Selective Determination of Vanillin in the Presence of Caffeine, its Electrochemical Behavior on an Au Electrode Electropolymerized with 3‐Amino‐1,2,4‐triazole‐5‐thiol

Abstract: Electrochemical oxidation of vanillin (VAN) in the presence of caffeine (CAF) was studied on a gold (Au) electrode modified with 3‐amino‐1,2,4‐triazole‐5‐thiol (ATT) film by using differential pulse voltammetry (DPV) and cyclic voltammetry (CV) method. The formation of the ATT film on the Au electrode surface was characterized by the CV, fourier transform infrared spectroscopy (FTIR) and impedance spectroscopy (EIS) methods. A single irreversible oxidation peak of the VAN was obtained by using the CV method. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 62 publications
0
6
0
1
Order By: Relevance
“…The nonlinear relationship between ν and the I pa was shown in Figure 6B. This result showed the oxidation process on the 35DT-GC modified electrode was diffusion-controlled [62]. In Figure 6C, I pa values were proportional to ν 1/2 over the range of 0.01-0.5 V s À 1 with linear regression equations: Ipa(μA) = 63.387v 1/ 2 (V s À 1 ) + 0.1076 (R 2 = 0.9987) and Ipa(μA) = 85.638v 1/ 2 (V s À 1 ) + 0.0571 (R 2 = 0.9983), respectively.…”
Section: Effect Of the Scan Rate On The Oxidation Of L-dopa And Parmentioning
confidence: 83%
See 1 more Smart Citation
“…The nonlinear relationship between ν and the I pa was shown in Figure 6B. This result showed the oxidation process on the 35DT-GC modified electrode was diffusion-controlled [62]. In Figure 6C, I pa values were proportional to ν 1/2 over the range of 0.01-0.5 V s À 1 with linear regression equations: Ipa(μA) = 63.387v 1/ 2 (V s À 1 ) + 0.1076 (R 2 = 0.9987) and Ipa(μA) = 85.638v 1/ 2 (V s À 1 ) + 0.0571 (R 2 = 0.9983), respectively.…”
Section: Effect Of the Scan Rate On The Oxidation Of L-dopa And Parmentioning
confidence: 83%
“…The CV technique gives some information about the changing interface of the electrode after modification of the surface [62]. The CV method was used to determine the efficiency of the fabrication of modified electrode and the effective surface areas of bare GC and 35DT-GC electrodes.…”
Section: Determination Of the Surface Areamentioning
confidence: 99%
“…Therefore, it can be concluded that the oxidation process of vanillin at FePc MOF/GCE involves two protons and two electrons, which is consistent with previously reported results. [50][51][52] The proposed mechanism for vanillin oxidation is shown in Scheme 2.…”
Section: Effect Of Scan Ratementioning
confidence: 99%
“…Table 1 [27–33] gives the comparison of VA sensors with proposed sensor. PTOMCNPE provides lower LOD as compared to gold electrode/ 3‐amino‐1,2,4‐triazole‐5‐ thiol, [28] Cajeput tree bark derived activated carbon/GCE, [29] arginine/graphene/GCE, [30] screen‐printed electrode/CNT, [31] and graphene paste/CTAB, [32] PNMCNTPE [34] and near LOD to T3T−Au/GE [33] . The developed sensor is relatively simple and low cost with high sensitivity.…”
Section: Resultsmentioning
confidence: 99%